2013
DOI: 10.1111/ijac.12009
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Dielectric Characteristics of Polyvinyl Alcohol (PVA) Interfacial Layer in Au/PVA/n‐Si Structures by Bi2O3Disperse

Abstract: Dielectric characteristics such as dielectric constant (ε′), dielectric loss (ε″), dielectric loss tangent (tanδ) and real and imaginary parts of electrical modulus (Μ′ and Μ″), and ac electrical conductivity (σac) of Au/ Polyvinyl Alcohol (PVA) (Bi2O3‐dispersed)/n‐Si structures have been investigated by using admittance measurements. Results show that the ε′ values of Au/PVA/n‐Si with Bi2O3‐dispersed PVA interfacial layer are very higher compared with those with pure and other dopant/mixture's of PVA. Thus, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Over the last decade, various types of metal‐insulator‐semiconductor (MIS) structures have been investigated vastly by many researchers . Metal‐polymer‐semiconductor (MPS) structures are used as an alternative to conventional MIS structures.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Over the last decade, various types of metal‐insulator‐semiconductor (MIS) structures have been investigated vastly by many researchers . Metal‐polymer‐semiconductor (MPS) structures are used as an alternative to conventional MIS structures.…”
Section: Introductionmentioning
confidence: 99%
“…Metal‐polymer‐semiconductor (MPS) structures are used as an alternative to conventional MIS structures. Main reason of using MPS structures is that having an organic interfacial layer between metal and semiconductor, rather than an inorganic one, leads to improvements in the electrical and dielectric properties of the structure . Also, the fact that MPS structures exhibit characteristics that are similar to those of MIS structures allows us to obtain the electrical characteristics of MPS structures the same way we obtain those of MIS structures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such advantages enable depositions to be performed over a large area at relatively low temperature. PVA is semicrystalline, watersoluble with low electrical conductivity polymer and widely used as fiber mats, films, paper coatings, membranes, and so on, due to its excellent chemical and physical properties, nontoxicity, processability, good chemical resistance, wide range of crystallinity, and good film formation capacity [13]. Shao et al [14] reported the thin PVA/zirconium oxychloride composite fibers prepared by using sol-gel processing and electrospinning techniques.…”
Section: Introductionmentioning
confidence: 99%